How do we remediate blood banking/transfusion medicine fellows? - Julie Katz Karp; Evelyn M. Potochny; Annette J. Schlueter; Nataliya Sostin; Jensyn Cone Sullivan; Andrea M. McGonigle; Evan M. Bloch; Hlaing Tint; Justin Kreuter; Mark K. Fung (Transfusion, 2026)
Abstract Background Remediation of physician learners is not infrequently discussed in the graduate medical education (GME) literature. However, none of this literature is specific to blood banking/transfusion medicine (BB/TM) fellows and their typical 1‐year fellowship program. Identifying a fellow's deficiencies and establishing an effective remediation program during a time‐limited BB/TM fellowship is challenging. Study Design and Methods GME literature on remediation of physician learners was reviewed. A group of current and former BB/TM fellowship directors convened virtually to discuss if and how this literature could apply to BB/TM fellowships. Possible best practices in the remediation of BB/TM fellows were then recommended. Results Challenges in the remediation of BB/TM fellows were identified, including the limited duration of the fellowship, the often‐small number of faculty available for remediation activities, and faculty unfamiliarity with remediation techniques. Beyond these challenges, many remediation best practices can be gleaned from the GME literature, including adequately documenting a fellow's deficiencies and any remediation programs implemented, as well as involving institutional GME leadership early in remediation efforts. Discussion Remediation of any physician learner can be difficult, but remediation of BB/TM fellows has unique challenges. Providing discipline‐specific insights into remediation may make the remediation of BB/TM fellows more effective and improve the competency of future physicians in the field.